To solve the equation for y, we need to isolate the variable y on one side of the equation.
−1 over 5y + 3 = −7
We can start by subtracting 3 from both sides of the equation:
−1 over 5y = −7 - 3
−1 over 5y = -10
To remove the fraction, we can multiply both sides of the equation by the denominator of the fraction, which is 5:
5 * (−1 over 5y) = 5 * -10
The 5 on the left side of the equation cancels out with the 5 in the denominator:
-1y = -50
Since -1 multiplied by any number is just that number, we can simplify further:
y = -50
Therefore, the solution to the equation is y = -50.
Solve the equation for y.
−1 over 5y+3=−7
50
-35
15
55
1 answer